Effects of Form‐Focused Training on Running Biomechanics: A Pilot Randomized Trial in Untrained Individuals. Issue 8 (26th January 2015) - Kumar, Deepak; McDermott, Kelly; Feng, Haojun; Goldman, Veronica; Luke, Anthony; Souza, Richard B.; Hecht, Frederick M.
Abstract: Objective: To investigate the changes in running biomechanics after training in form‐focused running using ChiRunning versus not‐form focused training and self‐directed training in untrained individuals. Design: Pilot study‐randomized controlled trial. Setting: Research institution with tertiary care medical center. Participants: Seventeen subjects (9 men, 8 women) with prehypertension. Methods: Twenty‐two participants were randomized to 3 study arms but 17 completed the study. The study arms were: (1) group‐based Form‐Focused running using ChiRunning (enrolled, n = 10; completed, n = 7); (2) group‐based conventional running (enrolled, n = 6; completed, n = 4); and (3) self‐directed training with educational materials (enrolled, n = 6; completed, n = 6). The training schedule was prescribed for 8 weeks with 4 weeks of follow‐up. All subjects completed overground running motion analyses before and after training.ClinicalTrials.gov identifier for this study isNCT0158718 . Outcomes: Ankle, knee, hip joint peak moments, and powers; average vertical loading rate (AVLR); impact peak; cadence; stride length; strike index; and stride reach. Paired t tests were used to compare differences within groups over time. Results: Form‐focused group reduced their Stride Reach ( P = .047) after the training but not the other groups. Form‐focused group showed a close to significant reduction in knee adduction moment ( P = .051) and a reduction in the peak ankle eversion moment ( P = .027). Self‐directed group showed an increase in the running speed ( P = .056) and increases in ankle and knee joint powers and moments. Conclusions: There are differences in the changes in running biomechanics between individuals trained in running form that emphasizes mid‐foot strike, greater cadence, and shorter stride compared with those not trained in the these techniques. These differences may be associated with reduced lower extremity stress in individuals trained in this running form, but more studies are needed to confirm these findings in larger samples.